Measuring Customer Loyalty Using Net Promoter Score: Analysis in Insurance Companies - Nauva Marin; Maria Assumpta Wikantari; Yudi Nur Supriadi (Green Publisher Indonesia, 2025)
The insurance industry operates in a highly competitive environment, where understanding customer loyalty is crucial for strategic business development. The Net Promoter Score (NPS) serves as a key performance indicator to gauge customer loyalty by measuring their likelihood to repurchase and recommend services. This study focuses on analyzing NPS implementation in Indonesian insurance companies to identify factors influencing customer loyalty and areas for improvement. The research objectives include evaluating the impact of customer experience, market segmentation, and loyalty-supporting factors on NPS scores. Data were collected through an NPS survey conducted from May to September 2023, targeting 1,195 valid respondents from 25 branches across Indonesia. The survey assessed customer perceptions across 13 product and service dimensions, including product diversity, claim process ease, and digital service support. Findings revealed an NPS score of 62.43, significantly higher than the industry average, indicating strong customer loyalty. Key strengths included certainty of benefits and clarity of service flow, while weaknesses were identified in digital service support and claim settlement speed. Segmentation analysis showed variations in loyalty by customer type, gender, age, and tenure. The study highlights the need for targeted improvements in digital services and claims processes, alongside better data distribution across branches. Implications suggest that insurers can enhance loyalty by addressing identified weaknesses and leveraging strengths in promotional campaigns. This research provides foundational insights into NPS effectiveness in Indonesia’s insurance sector, offering actionable recommendations for industry practitioners